2018
DOI: 10.1186/s40066-018-0216-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive values of seven high priority indigenous fodder tree species in pastoral and agro-pastoral areas in Eastern Ethiopia

Abstract: Background: Indigenous tree and shrub species are critical feed resources for the pastoralist and agro-pastoralist areas in Ethiopia. Nutritional and mineral composition of seven high priority leguminous indigenous tree species, (Acacia nilotica, Acacia tortilis and Tamarindus indica) and non-leguminous species (Berchemia discolour, Cordia sinensis, Dobera glabra and Ziziphus spina-christi) were characterized to inform decisions on the species utilization and domestication. Method: Data on a total of 17 nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
12
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 22 publications
(37 reference statements)
13
12
11
Order By: Relevance
“…In the present study, the foliar content of K was generally three times the requirement for small ruminants. These results are consistent with those reported by DERERO & KITAW (2018), where potassium was the macromineral with the second highest concentration after Ca in fodder tree species in pastoral and agropastoral areas in eastern Ethiopia. DOMÍNGUEZ-GÓMEZ et al (2014), reported similar results in semi-arid regions in northeastern of Mexico and HABIB et al (2016), in arid and semi-arid rangelands of northern Pakistan and suggested that sodium supplementation, could avoid deficiencies caused by high concentrations of K.…”
Section: Sitesupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the foliar content of K was generally three times the requirement for small ruminants. These results are consistent with those reported by DERERO & KITAW (2018), where potassium was the macromineral with the second highest concentration after Ca in fodder tree species in pastoral and agropastoral areas in eastern Ethiopia. DOMÍNGUEZ-GÓMEZ et al (2014), reported similar results in semi-arid regions in northeastern of Mexico and HABIB et al (2016), in arid and semi-arid rangelands of northern Pakistan and suggested that sodium supplementation, could avoid deficiencies caused by high concentrations of K.…”
Section: Sitesupporting
confidence: 93%
“…), which are the most common known uses as documented by ESTRADA-CASTILLÓN et al (2018). Livestock production based on grazing occurs mainly in arid and semi-arid regions, on land traditionally considered unsuitable for crop production, containing woody and shrubs plants relevant as potential fodder source (ESTELL et al, 2012), which contain satisfactory levels of protein and minerals for grazing ruminants, while maintaining or improving grassland availability (RAMÍREZ-ORDUÑA et al, 2005;GUERRERO-CERVANTES et al, 2012;HABIB et al, 2016;DERERO & KITAW, 2018). Many trees and shrubs of leguminous species of the semi-arid regions are used as feed especially due to the behavior in extensive grazing by goats and sheep (SANON et al, 2007) and also by wild ruminants, since shrub species remain green and with a relatively high nutrient content throughout the year (GUERRERO-CERVANTES et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The higher NDF content of A. toritlis leaves from this study is might be due to harvested leaves samples were at advanced age which had contained more stem parts which is responsible to higher NDF content. The NDF content of A. tortilis leaves in this study was higher than reported value of (338.4g/kg, DM) by [12], but lower than reported value of (506g/kg, DM) by [43]. The NDF content of A. seyal and A. albida leaves in this study were lower than reported values of (684.43g/kg, DM) and (512.8g/kg, DM) by [30], respectively.…”
Section: Chemical Compositioncontrasting
confidence: 83%
“…The CP concentration of A. albida leaves in this study was lower than reported values of (201.80g/kg, DM) and (197g/kg, DM) reported by [30] and [31], respectively. The CP concentrations of A. toritlis, A. nilotica and A. senegalensis leaves from this study were lower than reported CP concentrations of (152.9g/kg, 157.6g/kg, 159.3g/kg, DM) by [12], respectively but CP concentration for B. disclour in this study was higher than reported value of (116.4g/kg, DM) by same author. The CP level for C. molle from this study was lower than reported value of (160g/kg, DM) by [32], but CP concentration for G. tenax was higher than value of (93g/kg, DM) by the same author.…”
Section: Chemical Compositioncontrasting
confidence: 76%
See 1 more Smart Citation